Different populations of DNA polymerase alpha in HeLa cells. - Jackson, D; Cook, P (1986)
Three different populations of HeLa DNA polymerase alpha have been distinguished using a novel preparation of chromatin isolated using an isotonic salt concentration, which contains intact DNA. One synthesizes DNA in vitro at 85% of the rate in vivo, is found only in S-phase nuclei tightly associated with the nucleoskeleton and requires unbroken DNA in the form of chromatin as a template: we assume this is the authentic S-phase activity. On incubation at 37 degrees C, this activity dissociates from the nucleoskeleton to give a soluble activity that prefers broken templates. This soluble activity is in turn heterogeneous, containing active complexes of about 0 X 75 X 10(6) and 3 X 10(6) Mr. The third activity is also soluble and released by lysing cells at any stage of the cell cycle. It, too, prefers broken templates. The authentic activity is obscured by the soluble ones if broken templates are provided.